2020
DOI: 10.1108/afr-01-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' preferences and willingness to pay for microcredit in Benin: results from in-the-field choice experiments in Benin

Abstract: PurposeThis document analyses farmers' preferences and willingness to pay (CAP) for microcredit, in order to facilitate their access in rural areas.Design/methodology/approachData are based on a discrete choice experiment with 400 randomly selected farmers from 20 villages of the 7 Benin agricultural development hubs (ADHs). The preference choice modelling was performed using mixed logit (MXL) and latent class logit (LCL) models. Farmers' willingness to pay for each preferred attribute was estimated. The endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 50 publications
3
16
2
Order By: Relevance
“…(2021) also used mixed logit and conditional logit to analyze farmers' demand and willingness to pay for crop insurance. Ogouvide et al . (2020) applied the mixed logit and latent class model to study the demand for agricultural credit by farmers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2021) also used mixed logit and conditional logit to analyze farmers' demand and willingness to pay for crop insurance. Ogouvide et al . (2020) applied the mixed logit and latent class model to study the demand for agricultural credit by farmers.…”
Section: Methodsmentioning
confidence: 99%
“…For example, credit size and transaction costs were considered by Ding and Abdulai (2018) in designing the profile of agricultural credit demand. Unlike the study of Ding and Abdulai (2018), the method used by Ogouvide et al . (2020) to categorize the characteristic of credit duration in Benin is different from the standard norms as defined by financial institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries, particularly households in rural communities, agricultural activities represent the main source of income. Thus, economic theory has shown that access to finance reduces the financial constraints of producers and facilitates their access to productive technological inputs (Diagne, 1999a, b; Levine et al ., 2000; Ogouvide et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also addressed microcredit and its impact on the country. For instance, when analyzing farmers' demand for credit, Ogouvide et al (2020) found that farmers tend to prefer low-interest individual loans, in cash or a bundle of in cash and in-kind, disbursed before planting and with a duration of at least ten months. Flifli et al (2019) examined an innovative rice value chain financing system (VCFS) in Benin to identify the determinants of farmers' and processors' access to formal credit.…”
Section: Introductionmentioning
confidence: 99%